Parents' Assumptions and Beliefs about the Impact of Cultural Diversity on Children: A Preliminary Study in Italy, Bulgaria, Germany, Greece, and Spain - María Luisa Sierra-Huedo; Ana C. Romea; Lindsey A. Bruton (MDPI AG, 2024)
This study investigates parents' perceptions of the impact of cultural diversity on their children and their role in facilitating their children's navigation through diverse cultural landscapes. A questionnaire, part of the Erasmus+ REACT project (the reciprocal maieutic approach), was distributed among 243 parents of secondary school children in Bulgaria, Italy, Greece, and Spain. It aimed to shed light on the effects of cultural diversity on young individuals and the influence of parents in fostering intercultural competences and critical thinking. The findings reveal a strong positive perception among parents regarding cultural diversity, with a significant majority acknowledging its beneficial impact on their children's development. Parents identify themselves as crucial educators and role models, emphasizing the importance of open dialogue, positive exemplification, and the teaching of tolerance and respect. Despite recognizing the general adeptness of their children in interacting with cultural diversity, parents perceive challenges, particularly related to differences in beliefs, religions, and social classes. Parents favor experiential and participatory activities over traditional academic methods for fostering intercultural competence, suggesting a shift toward more inclusive educational practices that involve family and community. This study calls for educational initiatives that promote active participation, connection with the community, critical thinking, and empathy toward cultural differences.